Bibliography. - Dupont, Colin; Forss, Charlotta (Imago Mundi, 2021)
- ISSN 1566-3442 B 21:73.1(296) b B Stewart, Roger b Africa: A Group of Small Maps with Shields, 1690-1753 / Roger Stewart - I In i IMCoS, Journal of the International Map Collectors Society, 2020, B 160 b , 33-40: ill. - ISSN 0956-5728 B 21:73.1(297) b Brands of Nineteenth Century Antique Miniature Atlases / Roger Stewart. - I In i Mapping: Revista International de Geomática y ciencias de la tierra, 2019, B 195 b , 56-60: ill. - ISSN 1131-9100 B 21:73.1(222) b B Peral López, José b Las exposiciones en el Archivo General de Indias: La cartografía histórica del río Guadalquivir [= The exhibitions in the Archivo General de Indias: the historical cartography of the Guadalquivir River] / José Peral López and Maria Antonia Colomar Albájar. - I In i Caert-Thresoor, 2020, B 39 b , 1, 26-31: ill. - ISSN 0167-5001 B 21:73.1(304) b Voorstelling en potentieel van de kaartencollectie van de Universiteit van Amsterdam [= Presentation and potential of the map collection of the University of Amsterdam] / Reinder Storm and Bram Vannieuwenhuyze.